2017
DOI: 10.2166/wst.2017.277
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal content of Swedish municipal wastewater sludge – status and goals

Abstract: In 2014, 25% of the sludge produced at Swedish municipal wastewater treatment plants was applied to agricultural land. Even though the Swedish heavy metal limits for sludge to be used in agriculture are amongst the most stringent in the EU, more stringent heavy metal limits are proposed. Most sludge applied to agricultural land is recycled within a certification system, Revaq. Revaq has targets for control at source management and improvement of sludge quality. Statistics based on data collected within the Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 4 publications
0
9
1
Order By: Relevance
“…Although much of the SS in Europe is subject to control, it may still contain unwanted compounds (Bloem et al 2017). Certification systems such as Revaq in Sweden (Mattsson et al 2017), aimed at systematic control of sources, have helped to ensure that the quality of SS has considerably improved over time (Kirchmann et al 2017). Field studies at Petersborg have also shown that soil microorganisms can rapidly degrade organic compounds, as shown by the following two examples:…”
Section: Other Contaminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although much of the SS in Europe is subject to control, it may still contain unwanted compounds (Bloem et al 2017). Certification systems such as Revaq in Sweden (Mattsson et al 2017), aimed at systematic control of sources, have helped to ensure that the quality of SS has considerably improved over time (Kirchmann et al 2017). Field studies at Petersborg have also shown that soil microorganisms can rapidly degrade organic compounds, as shown by the following two examples:…”
Section: Other Contaminantsmentioning
confidence: 99%
“…European Union (EU) Directive 86/278/EEC, which sets limits for seven heavy metals, is currently being considered for revision (European Commission 2017). This is because many national authorities set lower limits for heavy metals than the EU directive, and also include organic contaminants (Inglezakis et al 2014;Mininni et al 2015;Mattsson et al 2017). Swedish regulations also limit phosphorus (P) and nitrogen (N) application rates with SS (Suppl.…”
Section: Introductionmentioning
confidence: 99%
“…The Fertilizer Product Act [30] and Decree [31] imposes maximum limit values on eight heavy metals (As, Cd, Cr, Cu, Ni, Zn, Pb and Hg) in sewage sludge used as a fertilizer product, which are given in Table 2. In Finland, the maximum limit values for the heavy metals listed above are more stringent than the maximum limit values allowed in the European Union [32]. Except for Hg (1.4 mg/kg d.m.…”
Section: Total and Bcr Extractable Heavy Metal Concentrations In The Sewage Sludgementioning
confidence: 92%
“…The species and concentrations of HMs in AD effluents are also highly depended on the feedstock (typically a mixture of animal manures and other organic wastes) and the specific ratio of the different WaW used. While stricter regulations are expected to minimize HM's in waste and wastewaters this is not always possible for every contaminant (Mattsson et al, 2017).…”
Section: 5mentioning
confidence: 99%